Exploring methods to maintain and improve captive big brown bat (Eptesicus fuscus) flight - Soljmosi, Renata (My University, 2025)
Wild-caught big brown bats (Eptesicus fuscus) experience increased mass, diminished ability to sustain flight, and increased take-off latency after three months in captivity, making them ineligible for flight experiments. These animals had been housed in small cages with ad libitum food. I quantified these changes by weighing and flying newly-caught E. fuscus, housing them under the mentioned conditions, and re-recording them after 11 weeks in captivity. I used LMMs to analyze data. Surprisingly, take-off latency decreased somewhat, though the existence of a true effect was inconclusive. Conversely, the bats had increased mass and decreased flight duration, as expected. The second part of this study examined methods, namely food availability and crawling exercise, to improve E. fuscus flight. I housed some subjects in a large colony space that allowed free flight, and I did not explicitly exercise them. I housed other subjects in small cages that restrict exercise, and exercised some through crawling, which I hypothesized would improve flight. Finally, I restricted some subjects’ food intake and gave ad libitum access to others. I hypothesized the restricted diet would improve flight, while ad libitum access would diminish it. I recorded flights three times per night, twice a week for 7.5 weeks. I analyzed the data using linear mixed-effects models. Restricting food intake had a positive effect on flight duration; ad libitum food access did not have a conclusive effect. Also, the crawling exercise did not positively affect flight; bats housed in the colony had increased flight duration. Apparently, having space for voluntary flight and being explicitly flown twice per week can improve flight. Take-off latency did not have conclusive results, though surprisingly, the bats on restricted diets had somewhat increased take-off latencies. In conclusion, restricting diet or explicitly flying bats housed in the colony are two methods that can be employed to improve flight duration to allow for scientific studies requiring flight.